Evaluation of sleep quality in patients with tinnitus (Annals of Medical Research, 2024)
Aim: Tinnitus occurs when a sound is detected in the ear in the absence of external auditory stimuli. It can impact daily activities, leading to issues with concentration, emotional distress, and sleep disturbances. The objective of this study is to examine the state of sleep quality in patients with tinnitus.Materials and Methods: A total of 81 patients (42 females, 39 males) who presented to the clinic within the past six months and had experienced subjective tinnitus for at least six months were included in the study. The Tinnitus Handicap Index (THI), Pittsburgh Sleep Quality Index (PSQI), and Insomnia Severity Index (ISI) questionnaires were utilized.Results: There was a moderate statistically correlation between THI and both PSQI (r=0.411; p=
Keywords: Tinnitus; Sleep quality; Questionnaire